2020
DOI: 10.1021/acs.jafc.9b07251
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Nanoparticle Matter in Red Wines Using Asymmetrical Flow Field-Flow Fractionation

Abstract: The particle matter of wine is mainly composed of wine colloids and macromolecules. The present work develops a methodology using asymmetrical flow field-flow fractionation coupled with multi-angle light scattering, differential refractive index detector, and ultraviolet detector (AsFlFFF–MALS–dRI–UV) for the fractionation and determination of the molar mass, the hydrodynamic radius, and the apparent densities of the aggregates and macromolecules present in wine samples. The results from a set of six Argentini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…9,28,29 The polysaccharide composition found in our wine colloids was comparable to the findings of other authors, which reported predominant levels of rhamnose, arabinose, galactose, glucose, mannose, and galacturonic acid as well as minor amounts of fucose, xylose, and glucuronic acid. 8,16,30,31 In total, the amounts of polysaccharides in the colloids increased from must (281−572 g/kg dry matter) to wine (435−806 g/kg dry matter). The yeast colloid contained 635 g of polysaccharides per kg of dry matter (Table S4).…”
Section: Musts Andmentioning
confidence: 99%
See 2 more Smart Citations
“…9,28,29 The polysaccharide composition found in our wine colloids was comparable to the findings of other authors, which reported predominant levels of rhamnose, arabinose, galactose, glucose, mannose, and galacturonic acid as well as minor amounts of fucose, xylose, and glucuronic acid. 8,16,30,31 In total, the amounts of polysaccharides in the colloids increased from must (281−572 g/kg dry matter) to wine (435−806 g/kg dry matter). The yeast colloid contained 635 g of polysaccharides per kg of dry matter (Table S4).…”
Section: Musts Andmentioning
confidence: 99%
“…Multiple colloid populations in variable sizes have also been described by the use of asymmetrical flow field-flow fractionation for colloid separation in the wine directly instead of size exclusion chromatography for the separation of isolated colloids. For instance, Osorio-Macı ́as et al 38 reported three colloid fractions with different UV-absorption behavior in a white wine, while Marassi et al 15 and Osorio-Macı ́as et al 16 found two colloid fractions with different UV-absorption behavior in red wines.…”
Section: Trammentioning
confidence: 99%
See 1 more Smart Citation
“…For the evaluation of the fate of phenolic compounds, for example, during fruit juice processing, the experimental setup must be extended by a certain kind of fractionation step such as centrifugation or equilibrium dialysis . Recently, the fractionation of wine colloids and particles composed of polyphenols, proteins, and polysaccharides has been analyzed by asymmetrical flow field-flow fractionation . This method seems particularly suitable for the investigation of aggregates because it allows the separation and, in combination with respective detectors, the characterization of particle properties.…”
Section: Mechanisms Of Interactionsmentioning
confidence: 99%
“…23 Recently, the fractionation of wine colloids and particles composed of polyphenols, proteins, and polysaccharides has been analyzed by asymmetrical flow field-flow fractionation. 24 This method seems particularly suitable for the investigation of aggregates because it allows the separation and, in combination with respective detectors, the characterization of particle properties. However, other less abundant chromatographic methods like countercurrent chromatography and centrifugal precipitation chromatography or capillary electrophoresis might be applied because they also allow a more or less nondestructive separation of the aggregates.…”
Section: ■ Mechanisms Of Interactionsmentioning
confidence: 99%